Assessment of Selected Serum Electrolyte and Associated Risk Factors in Diabetic Patients - Woyesa SB (Dove Medical Press, 2020)
Shiferaw Bekele Woyesa, Waqtola Cheneke Gebisa, Delebo Lefebo Anshebo Jimma University, Institute of Health Science, School of Medical Laboratory Science, Jimma, EthiopiaCorrespondence: Shiferaw Bekele Woyesa Tel +251471111875Email bekeleshiferaw@yahoo.comPurpose: The objective of this study was to assess selected serum electrolytes imbalance and associated factors in diabetic patients attending their follow up appointments in Jimma University Medical Center (JUMC) from February 1 to April 1, 2019.Patients and methods: A cross sectional study design was used to assess the selected serum electrolytes in diabetic patients attending their follow up appointments at Jimma University Medical Center (JUMC) chronic illness clinic. A convenience sampling technique was used to include 279 diabetic patients in the study and an interviewer based questionnaire was used to include all necessary data from each diabetic patient. Five milliliters of blood were collected from each subject and processed and analyzed for blood glucose and serum electrolyte determination by ABX Pentra400 and Humalyte plus5 ion-selective electrode (ISE) system  clinical chemistry analyzers. Pearson’s correlation coefficient model and multivariate logistic regression were used respectively to assess the correlation and significant association between abnormal serum electrolytes and independent variables.Results: A high prevalence of one or more serum electrolyte abnormalities was determined in diabetic patients. The overall prevalence was 42.0% (n=116/276) in which hyponatremia was the highest followed by hypochloremia and hypercalcemia, 40.6%, 14.9% and 10.9% respectively. Age, type of medication, and high body mass index (BMI) had strong positive correlations with abnormal serum concentration levels of sodium (r=0.611, P=0.731), potassium (r=0.752, P=0.812) and chloride (r=0.645, P=0.459). Being employed (AOR: 3.933, 95% C.I: 1.057–14.637, P value: 0.041), treated with mixed medications (AOR: 2.9, 95% C.I: 1.292–6.441, P value: 0.010) and being unable to control blood glucose level or being hyperglycemic (AOR: 3.2, 95% C.I: 2.179–5.721, P value: 0.000) were statistically identified as risk factors for serum electrolyte abnormalities in diabetic patients.Conclusion: The serum electrolyte concentration level was highly abnormal in diabetic patients. The prevalence of abnormal concentration was more common in diabetic patients with advanced age, and some variables had strong positive correlation with abnormal serum electrolyte level in diabetic patients.Keywords: hyperkalemia, diabetic patients, hyponatremia, Jimma University